What we are like when we are at our best: Appreciative stories of staff in a community mental health center - Salyers, Michelle P. (Am J Psychiatr Rehabil, 2015)
Appreciative Inquiry is an organizational change methodology that discovers what works well in an organization and then pursues strategies to enhance those factors. The initial discovery process itself provides data ripe for qualitative analysis. Narratives were collected from 27 community mental health staff about times when they were at their best. An emergent, consensus-based analysis was used to understand the stories and exemplary work -- with competent, caring staff and elements needed to support them. Findings are discussed in light of self-determination theory that people are at their best with a sense of mastery, connection, and autonomy.